(untitled) (Simbiótica. Revista Eletrônica, 2016)
The objective of this study is to understand the discursive behavior of federal deputies of the PT about the Welfare reform of the government Cardoso, held in 1998. For the analysis, they were used the aspects theoretical and methodological of theoretical discourse of Ernesto Laclau and Chantal Mouffe (2004), among which are the discourse of concepts, antagonism and hegemony. From this analysis could be seen, critically, the discursive construction of the deputies of the PT, featuring thus an antagonistic relationship between the political parties. Keywords: Theory of discourse; Workers party; Cardoso government; Welfare reform.